1988
DOI: 10.1103/physrevb.38.2504
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the 110-K superconducting transition in the Bi-Sr-Ca-Cu-O system

Abstract: Superconducting critical transitions with an onset at 112 K and zero resistance at 107 K are obtained within the Bi-Sr-Ca-Cu-0 system. The synthesis and formation of the 110-K superconducting phase using the 85-K material as a precursor is explained. The 110-K phase grows from the 85-K phase such that the resulting faceted crystal (a pseudomorph)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(58 citation statements)
references
References 10 publications
2
55
0
1
Order By: Relevance
“…A classical experimental study of the role of magnetic impurities in conventional superconductors was carried out 24 and followed by many in details. [25][26][27][28] Since the discovery of Bi-Sr-Ca-Cu-O high-Tc superconducting system, [29][30][31] besides modifying the 'Tc', great progress has been achieved in changing the structural properties of Bi-based superconductor by varying composition and processing condition (temperature, pressure, environment etc.). Among the various techniques for structural/microstructural modification even the phase control also, substitution/doping is believed to be the most promising.…”
Section: Introductionmentioning
confidence: 99%
“…A classical experimental study of the role of magnetic impurities in conventional superconductors was carried out 24 and followed by many in details. [25][26][27][28] Since the discovery of Bi-Sr-Ca-Cu-O high-Tc superconducting system, [29][30][31] besides modifying the 'Tc', great progress has been achieved in changing the structural properties of Bi-based superconductor by varying composition and processing condition (temperature, pressure, environment etc.). Among the various techniques for structural/microstructural modification even the phase control also, substitution/doping is believed to be the most promising.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of the 110 K superconducting phase Bi2Sr2Ca2Cu30y (Bi-2223) in 1988 [1,2], a great deal of research has been focused on optimization of its phase purity and microstructure . Lead addition to the Bi-Sr-Ca-Cu-0 system was shown to stabilize the Bi-2223 phase and also accelerate the phase formation kinetics [7-91. Other related studies revealed that the lead content is a critical variable in fabricating tapes by the two-powder process [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the needle-like grains are the low T c phase (2201) , and the platelike structures are the high T c phases (89)(90)(91). After the BC treatment , part of this surface was changed , but some plate- (a) before and (b) after exposure in the ball istic compressor.…”
Section: Sem Investiqationsmentioning
confidence: 99%
“…These revealed a new class 。 f materials to be explored. In the 75 years following the discovery of superconductivity , the transition temperature T c had been gradually increased from the 4.2 K for Hg to 23 (15) announced that a ceramic oxide compound in the Y-Ba-Cu-O system becomes a superconductor at a temperature as high as 90 K (called high temperature superconductor , HTSC). In about 12…”
Section: ) Heavy Fermion Superconductors Such As Ube I3 Etc T C mentioning
confidence: 99%